ANALYSIS OF THE REASONS FOR THE ENROLMENT IN THE PROFFESIONAL STUDY PROGRAM AT FACULTY OF SPORT AND PHYSICAL EDUCATION - Jelisaveta Kalajdžić; Višnja Đorđić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Faculty of sport and physical education in Novi Sad enrolled first generation at proffesional study program three years ago. In past period no objective analysis of effi-ciacy and justifiableness of proffesional courses has been conducted. Aiming to explane some aspects of that issue, the authors analyse the students' reasons for the enrolment in the proffesional study program. The students assessed the importance which they personaly attach to the 20 offered reasons for the enrolment in the proffesional courses. The degrees of importance of the offered reasons were determined. The results of the research can be applied in evaluating justifiableness of proffesional studies.